If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 2(4y + -3) = 40 Reorder the terms: 14 + 2(-3 + 4y) = 40 14 + (-3 * 2 + 4y * 2) = 40 14 + (-6 + 8y) = 40 Combine like terms: 14 + -6 = 8 8 + 8y = 40 Solving 8 + 8y = 40 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 8y = 40 + -8 Combine like terms: 8 + -8 = 0 0 + 8y = 40 + -8 8y = 40 + -8 Combine like terms: 40 + -8 = 32 8y = 32 Divide each side by '8'. y = 4 Simplifying y = 4
| 196=-16t^2+18t+224 | | -3(2)-(-3)= | | 2x^2-6x=3 | | 3(-2)+2= | | x^4-8x^2+16=9 | | 3n+5=-21 | | x^4+8x^2+16=9 | | -2x+7=-53-7x | | x^2+8x^2+16=9 | | 8x+7x-x=42 | | 5(a+3)-2(a+3)=7 | | 2u-6=-14 | | x+13x=42 | | 13h-11-h=4-27h-2 | | 6(x-3)=4x+12 | | 6-5(2n-3)=1 | | -14m-16=2(23-7m) | | 1200=780+5x | | 3x^2-13x=-10 | | 5n-18-n=2(2n-9) | | 450=6h+120 | | 4x^2+12= | | 4x+2x=-20 | | -3x+7=3(-1x+2) | | 4(2x-3)=5x+7+3x | | -23=3p+5p+p | | 5x+1=-3x+9 | | 3.4+.72x=6.7x-1.39 | | f(-2)=-2*2-4x+3 | | x^2-22x+121=125 | | 3x^2-2=16 | | 3x*2-2=16 |